The scale and the dynamics of permanent migration in rural and peri-urban areas in Poland – some problems - Biegańska Jadwiga; Szymańska Daniela (Bulletin of Geography. Socio-Economic Series)
This article refers to the analysis and the evaluation of permanent migration as observed in rural areas of Poland, especially in peri-urban areas of the Polish cities between the years 1995 and 2011. The article covered all 2,173 rural and rural-urban (excluding urban parts) gminas in the country. In the article there were shown what are the migration volumes and dynamics in rural areas and what is the situation of large cities’ peri-urban areas in terms of permanent migration.